Growth Dynamics, Yield and Economics of Pearl Millet (Pennisetum glaucum) as Influenced by Vermicompost and Fertilizers - Narolia, R S; Poonia, B L (Annals of Arid Zone, 2016)
A study was conducted during rainy seasons of 2003 and 2004 at College of Agriculture, Bikaner, to study growth dynamics, yield and economics of pearl millet (Pennisetum glaucum (L.) R.Br. Emend Stunz) as influenced by vermicompost and fertilizers. The results revealed that plant height, dry matter accumulation, total number of tillers at 40 DAS, yield attributes, physiological parameters, seed and stover yield, harvest index, nutrient uptake, net returns and B:C ratio increased significantly due to drilling of vermicompost @ 2 t ha-1 over control, where as its drilling @ 1 t ha-1 remained statistically at par with soil incorporation @ 2 t ha-1. Maximum and significantly higher growth parameters, yield attributes, physiological parameters, yield, HI, nutrient uptake, net return and B:C ratio were recorded due to application of 90 kg N + 45 kg P2O5 ha-1 as compared to control (N0 P0). Key words: Fertilizers, pearl millet, vermicompost, physiological parameters, economics.